Web Applications with Elm Functional Programming for the Web - Loder, Wolfgang (Apress, 2018)
Learn the basics of the Elm platform for web applications. This book covers the language as of version 0.18, its fundamental building blocks, and the most important libraries. After reading this book you will have an understanding what Elm can do for you. Also, you will be able to build on the example in the book to develop advanced web applications with Elm. You will: Work with Elm and its development environment Learn the language and libraries in examples Use the Elm architecture to create applications with the Elm platform Put it all together with a sample application and explanation that covers the implementation details.